The time course for changes in oxidative stress and DNA in response to exercising in a hot environment: The relationship with VO2max - Knez, W. L.; Kelly, K. B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Exercising in a hot environment is associated with cardiovascular alterations such as an increase in core temperature, dehydration and cardiac drift. However, there is minimal research investigating the time course of changes in oxidative stress and DNA in response to exercise and thermal stress. Additionally, it is not known whether there is a critical point in core temperature for the production of oxidative stress or DNA modification, and whether this relationship is associated with an individual's maximal oxygen consumption (VO2max). Therefore, the first aim of this study was to investigate the time course of changes in indirect markers of oxidative stress and DNA modification during and after an aerobic bout of exercise in a hot environment. Secondly, we sought to determine whether there is a relationship between VO2max and the changes in markers of oxidative stress and DNA modification. Methods: Eight recreational cyclists (age=30.9±2.2yrs; height=177.9±4.1cm; mass=74.5±4.5kg) completed a cycling VO2max in hot conditions (35°C, 70%RH) to determine 60% of peak power output. One week later the participants returned to the laboratory and cycled at this intensity until they reached a core temperature of 38.5°C. Blood was sampled before, during, and after (0, 10, 25, 35, post 10 and post 20 mins) exercise to determine indirect markers of oxidative stress (malondialdehyde; MDA) and DNA (8-hydroxy-2'-deoxyguanosine oxidation; 8-OHdG) modification. Statistical analysis was completed using linear mixed models with a level of significance set at p.0.05. Results: Cycling at 60% of peak power output until core temperature reached 38.5°C resulted in an inverse relationship between VO2max and the production of MDA and 8-OHdG (p<0.047; p<0.001). Additionally, after adjusting for VO2max there was a significant increase in oxidative stress over the exercise bout. Data showed that MDA increased during exercise (0-10, 25, 35 min [0 min post]) and decreased from 0-post to post 20 min recovery. After correcting for multiple comparisons there was a tendency towards significance from 0 mins to the completion of the exercise bout. However, no changes were observed in the modification of DNA during exercise or recovery. No relationship was observed between changes in blood markers and core temperature. Discussion: Research shows that regular exercise protects against exercise-induced changes in oxidative stress and DNA. This research has also shown that this relationship extends to exercising in a hot environment. In this investigation, higher VO2max was associated with a decrease in both oxidative stress and DNA modification. Changes in oxidative stress appeared to be more sensitive to exercise duration than core temperature. Furthermore, these data showed that there was no critical core temperature for the development of oxidative stress. However, the current project was limited to a maximum core temperature of 38.5°C. Future research should continue exercise beyond this point with a larger sample to develop a clearer understanding.